Central bank digital currency adoption challenges, solutions, and a sentiment analysis - Peterson K. Ozili; Sergio Ná\~nez (Journal of Central Banking Theory and Practice, 2024)
We identify some factors limiting CBDC adoption and some of the possible solutions. We also assess the media sentiment about central bank digital currencies in general as well as about locally issued CBDCs. We find that there is a high correlation between the negative media sentiment about CBDCs in general and locally issued CBDCs. We also find that the negative media sentiment about the eNaira, DCash and Sand Dollar was caused by the existing negative media sentiment about CBDCs in general. However, a positive media sentiment about the eNaira, DCash and Sand Dollar was not caused by the existing positive media sentiment about CBDC in general.
Keywords: E31; E58; 330; CBDC; eNaira; DCash; Sand Dollar